State of the art on methodologies for the development of a metadata application profile - Malta, Mariana Curado (2013)
This article presents the state of the art on methodologies for the development of a metadata application profile. For this purpose we have performed searches in scientific on-line databases and made other efforts such as global searches on the Web and calls on the mailing lists of the metadata communities to find articles and Web pages about metadata application profiles development and metadata best practices or methodologies. These searches produced 21 items of which 9 have information on how the metadata application profiles were developed. As a result of this analysis we have found small formulas or private recipes for very particular phases of the process, but none is described in detail. We have also found guidelines that were too global and not sufficiently detailed for the metadata application profile development. As far as we could determine, there is no comprehensive methodological support for the metadata application profile development.